Mechanism of total saponins of Ranunculus ternatus Thunb. in treatment of breast cancer based on liquid chromatography–mass spectrometry and network analysis - Zhang, Yuanxin; Nan, Shuo; Zhao, Wei; Xie, Haisheng; Miao, Jinxin; Miao, Mingsan (Frontiers in Pharmacology, 2025)
ObjectiveTo explore the mechanism of total saponins of Ranunculus ternatus Thunb. (RT) in the treatment of breast cancer (BC) using liquid chromatography–mass spectrometry (LC-MS) technology and network analysis.MethodsThe metabolites of RT were detected using LC-MS. Metabolites and targets of RT and BC were identified in different databases, and potential targets and pathways were predicted using protein–protein interaction network and pathway enrichment analyses. A mouse model of BC created by cellular injection and MCF-7 cells were used as research objects for in vivo and in vitro validation experiments to study the anti-BC mechanism of RT.ResultsA Kyoto Encyclopedia of Genes and Genomes analysis showed that the Janus kinase/signal transducer and activator of transcription signaling pathway might be associated with the anti-BC effects of RT. The in vivo and in vitro experiments showed that Total saponins from RT had a good anti-BC effect that can inhibit the expression of JAK2 and STAT3-related proteins and mRNA, affect the expression levels of serum inflammatory factors tumor necrosis factor-α, interleukin-6, and interleukin-10, inhibit tumor growth, proliferation, and migration, and promote tumor cell apoptosis.ConclusionTotal saponins from RT may play a role in BC treatment by regulating the JAK2/STAT3 signaling pathway.